Cognitive Drivers of Investment Behavior: Analyzing the Mediation-Moderation Model on Herding Behavior among Gen-Z Investors - Siti Aisjah; Wildan Fadhila; Cicik Retno Wati; Atim Djazuli; Sri Palupi Prabandari (Universitas Negeri Semarang, 2025)
This study examined the influence of herding behavior on investment behavior with risk tolerance as a mediator and financial literacy as a moderator. Since Investment participation among young generations in Indonesia has grown significantly, yet behavioral biases such as herding continue to undermine rational decision-making Previous studies reported inconsistent findings regarding the direct impact of herding on investment behavior, leaving an important research gap. A quantitative approach was employed using survey data from 386 Gen Z investors in East Java, analyzed with SEM-PLS. The results confirmed that herding significantly affected both investment behavior and risk tolerance, while risk tolerance strongly influenced investment behavior and partially mediated the herding–investment link. Moreover, financial literacy strengthened the effect of herding on investment behavior. The findings imply that improving financial literacy and strengthening risk management education are essential for fostering rational investment decisions. Future research should expand the demographic scope and additional psychological and social factors to the model.